2011
DOI: 10.1038/sj.bjc.6606085
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density and its interaction with other breast cancer risk factors in an Asian population

Abstract: Background:Joint effects of mammographic density and other risk factors on breast cancer risk remain unclear.Methods:From The Singapore Breast Screening Project, we selected 491 cases and 982 controls. Mammographic density was measured quantitatively. Data analysis was by conditional logistic regression.Results:Density was a significant risk factor, adjusting for other factors. Density of 76–100% had an odds ratio of 5.54 (95% CI 2.38–12.90) compared with 0–10%. Density had significant interactions with body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 19 publications
8
59
0
1
Order By: Relevance
“…Secondly, it may be possible to reduce or even eliminate confounding with BMI by choosing an absolute (rather than relative) density measure. 37,38 Classic anthropo metric measures of adiposity (BMI and waist circumference) have been shown to be as good for adjusting density as adiposity measures from whole body estimated by dual x-ray absorptiometry and CT. 39 It is not yet clear whether relative or absolute breast density is a better predictor of risk. 22,25,38 Vachon et al 40 found that absolute dense area had a similar risk predictive potential as percent density.…”
Section: Breast Density and Breast Cancer Riskmentioning
confidence: 99%
“…Secondly, it may be possible to reduce or even eliminate confounding with BMI by choosing an absolute (rather than relative) density measure. 37,38 Classic anthropo metric measures of adiposity (BMI and waist circumference) have been shown to be as good for adjusting density as adiposity measures from whole body estimated by dual x-ray absorptiometry and CT. 39 It is not yet clear whether relative or absolute breast density is a better predictor of risk. 22,25,38 Vachon et al 40 found that absolute dense area had a similar risk predictive potential as percent density.…”
Section: Breast Density and Breast Cancer Riskmentioning
confidence: 99%
“…Known breast cancer risk factors such as late age at first birth, nulliparity, and postmenopausal hormone therapy are positively associated with mammographic density [7,8]. Increasing age, low parity, and body mass index (BMI), however, are negatively associated with mammographic density [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from Western countries have shown that women with extremely dense breasts (75 % or more dense tissue in breasts) have four to six times greater risk of developing breast cancer than women with fatty breasts (25 % or less dense tissue in breasts) [22][23][24][25][26][27][28][29][30]. Reports from Asian countries, mainly from Japan, have also identified dense breast tissue as a risk factor for breast cancer [31][32][33].…”
Section: Breast Density As a Risk Factor For Breast Cancermentioning
confidence: 93%